2017
DOI: 10.3390/cancers9090117
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cytokine Release in Ex Vivo Response to Cilengitide and Cetuximab Is a Marker for Improved Survival of Head and Neck Cancer Patients

Abstract: Targeting of αVβ3 and αVβ5 integrins by cilengitide may reduce growth of solid tumors including head and neck squamous cell carcinoma (HNSCC). Preclinical investigations suggest increased activity of cilengitide in combination with other treatment modalities. The only published trial in HNSCC (ADVANTAGE) investigated cisplatin, 5-fluorouracil, and cetuximab (PFE) without or with once (PFE+CIL1W) or twice weekly cilengitide (PFE+CIL2W) in recurrent/metastatic HNSCC. ADVANTAGE showed good tolerability of the cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Some reasons for the unexpected clinical low efficacy in glioblastoma could be related to the fast off-rate of cilengitide from its targets, the rapid plasma clearance, or the poor perfusion of the brain tumor environment (43). However, it is important to note that a beneficial therapeutic action was found when administered in association with standard radiotherapy or chemotherapy (125, 126), and this was also found in other type of tumors (127, 128).…”
Section: Thyroid Hormone Non-genomic Actions In T Cell Lymphomasmentioning
confidence: 99%
“…Some reasons for the unexpected clinical low efficacy in glioblastoma could be related to the fast off-rate of cilengitide from its targets, the rapid plasma clearance, or the poor perfusion of the brain tumor environment (43). However, it is important to note that a beneficial therapeutic action was found when administered in association with standard radiotherapy or chemotherapy (125, 126), and this was also found in other type of tumors (127, 128).…”
Section: Thyroid Hormone Non-genomic Actions In T Cell Lymphomasmentioning
confidence: 99%
“…First, we evaluated the effect of multiple cytokines on inducing PD-L2 expression, including epidermal growth factor (EGF), IL-8, IL-10, tumor necrosis factor (TNF-α), IL-6, which were correlated with the response to cetux treatment in HNSCC. [21][22][23][24] Among them, EGF significantly upregulated PD-L2 levels compared with other cytokines (online supplemental figure 4A). Furthermore, PD-L2 WT protein expression level was increased in response to EGF stimulation, whereas non-glycosylated PD-L2 4NQ mutant expression was not affected by EGF (online supplemental figure 4B).…”
Section: Egf/stat3 Signaling Drives Pd-l2 Glycosylation Through N-glycotransferase Fut8mentioning
confidence: 99%
“…To organize the current treatment options in clinical trials into clinically meaningful arms, we used general prespecified criteria, as shown in Table 1. Cilengitide (Cil) and cetuximab (Cet) are seldom used in NSCLC, and for statistical convenience and network simplification, Cil is categorized in the aVEGFR class, and Cet is categorized in the ET class [48].…”
Section: Definitions Of Outcomes and Treatment Armsmentioning
confidence: 99%